Pengaruh Tata Kelola Perusahaan Terhadap Volatilitas Laba (Studi Empiris Pada Perusahaan IPO di Indonesia) - Johanes Tarigan; Agus Zahron Idris (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
This study aims to determine the effect of institutional ownership, managerial ownership, and the proportion of independent commissioners on profit volatility in companies carrying out Initial Public Offerings (IPO) during 2018 - 2020 with sales growth as a control variable. The research method uses quantitative methods. The population in this study are companies that carry out Initial Public Offerings (IPO) on the Indonesian Stock Exchange. Based on the sample selection criteria, a sample of 152 companies was obtained. The data analysis technique used was descriptive statistical analysis, classical assumption test, F test and T test. The results showed that institutional ownership and managerial ownership had no effect on earnings volatility. Meanwhile, the disclosure of the proportion of independent commissioners has an effect on earnings volatility.